Maternal and neonatal outcome among women with early-onset preeclampsia and late-onset preeclampsia - Luthfi Rahman; Ruswana Anwar; Johanes Cornelius Mose (Taylor & Francis Group, 2024)
Objective This study aimed to determine the differences in characteristics and outcomes of early-onset and late-onset Preeclampsia.Methods A retrospective cross-sectional study was conducted on female patients giving birth with preeclampsia admitted into the Department of Obstetrics and Gynecology of Dr. Hasan Sadikin Hospital Bandung from January 2020 to December 2022 who met the study criteria. A total of 435 subjects met the inclusion criteria were divided into two groups: early-onset preeclampsia and late-onset preeclampsia. Differences in outcomes were analyzed using the Chi-square or Fisher test for categorical data and the T-independent or Mann-Whitney test for numerical data.Results There were differences in the incidence of HELLP syndrome (9.0 vs. 2.7%; p = 0.009), prematurity (77.7 vs. 21.4%; p = 0.000), early neonatal death (10.4 vs. 2.7%; p = 0.002), asphyxia (22.7 vs. 8.0%; p = 0.000), SGA (41.7 vs 21.9%; p = 0.000), and LBW (78.7 vs 40.2%; p = 0.000) in early-onset preeclampsia with late-onset. Length of stay was longer in early-onset preeclampsia cases (4.0 vs 3.0 days; p = 0.000). Increased ureum and liver enzymes results were significantly higher in early-onset preeclampsia.Conclusion There is a difference in the outcome of pregnant women with early-onset and late-onset preeclampsia. Women with early-onset preeclampsia tend to have more adverse maternal and neonatal outcomes. In terms of maternal outcome, they tend to have higher liver enzymes level and HELLP syndrome, while in terms of neonatal outcome they tend to have prematurity, early neonatal death, asphyxia, SGA, and LBW.